Analysis of The Implementation of Project-Based Learning Teaching Modules in Science Learning in Elementary Schools - Nurfida Nurfida; Afkar Afkar; Irdalisa Irdalisa (Al-Madrasah: Jurnal Ilmiah Pendidikan Madrasah Ibtidaiyah, 2026)
Project Based Learning based teaching module in Science learning in elementary school lies in the need to ensure the effectiveness of contextual learning. This study aims to analyze the application of Project Based Learning (PjBL) based teaching module in learning Natural and Social Sciences (IPAS) grade IV in Gugus 1 Peudada. This study uses a descriptive qualitative approach with data collection techniques through in-depth interviews, observations, in three elementary schools, namely UPTD SD Negeri 1 Peudada, UPTD SD Negeri 10 Peudada, and UPTD SD Negeri 12 Peudada. Qualitative data validity tests include credibility, transferability, dependability and confirmability tests. Data analysis was carried out using qualitative descriptive namely data reduction, data presentation and conclusions. The results of this study indicate that the completeness of the PjBL teaching module. The PjBL teaching module used by teachers is in the fairly complete category, but does not meet all the ideal components of the Independent Curriculum. Time constraints, facilities and infrastructure, student numbers, and differences in student abilities also hamper the optimization of PjBL in the classroom. The results of the obstacles and challenges in implementing PjBL face internal obstacles in the form of limited time, minimal practice facilities, heterogeneity of student abilities, and teacher skills in managing projects. In addition, there are external obstacles such as lack of parental support, an unsupportive home environment, economic limitations, and school policies that still emphasize academic achievement. These obstacles overall affect the effectiveness of implementing PjBL in science learning.